O fenômeno das organizações substantivas - Serva, Maurício (1993)
The article analyzes the phenomenon of substantive organizations, that also named collectivists or aliernatives. It shows the results of the research made in Salvador with twelve substantive organizations. lt also discuss the inappropriate of the substantive organizations approach in Administrative Theory and aims a option into review the theoretic approach, intending a renewal of the Theory in front of the news organizational phenomenons.